THE ROLE OF SUSTAINABLE BUSINESS PRACTICES ON THE PERFORMANCE OF MANUFACTURING FIRMS. - OLUKA ARNOLD POWELL (UGANDA CHRISTIAN UNIVERSITY., 2024)
Abstract. This dissertation explores the contribution of business sustainability practices at Coca-Cola Beverages Uganda Ltd, focusing on Corporate Social Responsibility, sustainable packaging, and water and energy efficiency. It looks at the three key facets of organizational performance: financial performance, corporate reputation, and customer retention. This research will explain how sustainability initiatives that affect operational efficiency, profitability, and stakeholders' perceptions are indicative of broader implications for long-term business success. It was a cross-sectional research design wherein both qualitative and quantitative methodologies were used. The population of the study included employees of Coca-Cola Uganda Ltd and external stakeholders, totaling 617 employees with a sample size of 238 participants, comprising employees from the three target departments: production, marketing, and sales. Krejcie and Morgan table and stratified random sampling technique ensure that the sample represents the subjects in different demographic and professional categories. Questionnaires were the only primary data collection means, designed to assess the perception of the respondents regarding the initiatives concerning company sustainability and the linkage of the performance. Quantitative and qualitative techniques were therefore applied to analyze the data collected, hence enabling an assessment of the role that sustainable practices play in the company's performance metrics. The findings of this study add to the understanding of how sustainability can be integrated into the business model for improved organizational outcomes by providing practical recommendations that will enhance sustainable practices of Coca-Cola Uganda Ltd. toward growth and retention.
A CASE OF COCA-COLA UGANDA LTD.